Proceso atención de enfermería en paciente adulto con pancreatitis aguda. - Litardo Gonzales, Guisela Mariuxi (2022)
The work presented is about the elaboration of a clinical case of a young, female patient, with acute pancreatitis of biliary origin, which presents in its severe state, with deterioration of its general hemodynamic state. The main objective of this work is the application of the nursing care process, and the execution of interventions according to the established diagnoses. The work is developed based on the follow-up of the clinical history from which the information is extracted, in addition to the bibliographic review for the elaboration of the theoretical framework. The results obtained were: the nursing care process and the interventions that determine the severity of the clinical case are applied. This work seeks to be an important source of learning in relation to a pathology that occurs above all in critical areas of health.